Photoactivated adenylyl cyclases attenuate sepsis-induced cardiomyopathy by suppressing macrophage-mediated inflammation - Xia, Guofang; Shi, Hongyu; Su, Yuanyuan; Han, Beibei; Shen, Chengxing; Gao, Shiqiang; Chen, Zhong; Xu, Congfeng (Frontiers in Immunology, 2022)
Sepsis-induced myocardiopathy, characterized by innate immune cells infiltration and proinflammatory cytokines release, may lead to perfusion failure or even life-threatening cardiogenic shock. Macrophages-mediated inflammation has been shown to contribute to sepsis-induced myocardiopathy. In the current study, we introduced two photoactivated adenylyl cyclases (PACs), bPAC and biPAC into macrophages to detect the effects of light-induced regulation of macrophage pro-inflammatory response and LPS-induced sepsis-induced myocardiopathy. By this method, we uncovered that blue light-induced bPAC or biPAC activation considerably inhibited the production of pro-inflammatory cytokines IL-1 and TNF-α, both in mRNA level and protein level. Furtherly, we assembled a GelMA-Macrophages-LED system to allow light to regulate cardiac inflammation in situ with murine models of LPS-induced sepsis. Our results showed significant inhibition of leukocytes infiltration, especially macrophages and neutrophils, suppression of pro-inflammatory cytokines release, and alleviation of sepsis-induced cardiac dysfunction. Thus, our study may represent an emerging means to treat sepsis-induced myocardiopathy and other cardiovascular diseases by photo-activated regulating macrophage function.